2008
DOI: 10.2174/138920008784220574
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific and Age-Dependent Bile Acid Composition: Aspects on CYP8B and CYP4A Subfamilies in Bile Acid Biosynthesis

Abstract: The present review aims to give an overview of the cytochrome P450 8B (CYP8B) and cytochrome P450 4A (CYP4A) subfamilies in relation to biosynthesis of bile acids, in particular trihydroxy bile acids. Trihydroxy bile acids are basically required in most species and have an impact on cholesterol and lipid metabolism. The primary trihydroxy bile acid in most mammals is cholic acid. Some species produce other important trihydroxy bile acids, for example the adult pig which produce hyocholic acid instead of cholic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 94 publications
0
15
1
Order By: Relevance
“…Current researches suggested that some CYP isoforms, such as CYP1A [8], CYP2B [9], CYP2C [10], CYP2D [11], participate arachidonic acid metabolism. CYP2C19, one human cytochrome P450 enzyme, is not only a clinically important metabolic enzyme responsible for the metabolism of a number of therapeutic drugs but also the key enzyme of EETs synthesis and abundantly expressed in endothelial and smooth muscle cells [12], [13] Recently, there were several studies concerning the CYP2C19 polymorphism and cancer susceptibility [14][17].…”
Section: Introductionmentioning
confidence: 99%
“…Current researches suggested that some CYP isoforms, such as CYP1A [8], CYP2B [9], CYP2C [10], CYP2D [11], participate arachidonic acid metabolism. CYP2C19, one human cytochrome P450 enzyme, is not only a clinically important metabolic enzyme responsible for the metabolism of a number of therapeutic drugs but also the key enzyme of EETs synthesis and abundantly expressed in endothelial and smooth muscle cells [12], [13] Recently, there were several studies concerning the CYP2C19 polymorphism and cancer susceptibility [14][17].…”
Section: Introductionmentioning
confidence: 99%
“…Cytochrome P450 (CYP) epoxygenases metabolize arachidonic acid to epoxyeicosatrienoic acids (EETs) (Node et al, 2001;Fichtlscherer et al, 2004;Lundell and Wikvall, 2008;Fava et al, 2008). CYP2C19 is one of the human cytochrome P450 enzymes, and it is abundantly expressed in endothelial and smooth muscle cells (Imig et al, 2000;Ercan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The gene encoding CYP8B1 is also highly regulated at the transcriptional level by many of the same mechanisms regulating CYP7A1. However, there some differences in the regulation of the genes encoding CYP7A1 and CYP8B1 ( 29 ). The enzymes in the bile acid biosynthetic pathway are located at many different cellular locations in the hepatocyte, including smooth endoplasmic reticulum, mitochondria, peroxisomes, and cytoplasm.…”
mentioning
confidence: 99%